Escuta e referencialidade. Composição em diálogo com o meio ambiente - Marcelo Ricardo Villena (2017)
From a theoretical research on two key concepts (listening and referentiality) three types of performative procedures are developed for compositions that seek to establish relationships between soundscapes and musical sounds produced with acoustic means. The concept of referentiality, aided by Intersemiotic Translation and Topical Theory, is used to understand the mechanisms implicit in the compositional act of connecting environmental stimuli with musical materials. The listening and environmental perception is evaluated as a methodology for composition planning, through the Ecological Theory of Perception (James Gibson), Ecological Listening (Eric Clarke) and Sensitive Listening (Marton). The work also accepts contributions from the reflection of the relations between music and the environment present in indigenous cultures (Aztec, kuikuro, kidsêjê, tikmu'un), the study of theoretical writings and / or listening to compositions by: Jonathan Kramer, Olivier Messiaen , Ulises Ferretti, John Cage, Peter Ablinger, Morton Feldman, David Monacchi, Lilian Nakahodo and Mathew Burtney. This theoretical study allows the elaboration of the three performance proposals mentioned above: 1) pieces for traditional acoustic instruments to be performed in a conventional concert situation; 2) pieces to be played through the manipulation of everyday objects, harvested in specific environments; And 3) pieces to be played in specific places, of indeterminate character, in which the flow of musical events is defined at the moment of execution from the listening of the environmental sonorities.